IMPLEMENTASI DIGITAL MARKETING BERBASIS WEB UNTUK MENINGKATKAN PEMASARAN UMKM SNEEW - Nauro Cahya Kanthi; Muhammad Amrulloh; Lukman Abdul Azizul Hakim (CV. Denasya Smart Publisher, 2026)
This study aims to implement website-based digital marketing for Sneew, a small and medium-sized enterprise (SME), to support marketing activities that previously relied on social media and word-of-mouth promotion. The research methods included needs analysis, website design and development, implementation of digital marketing strategies, and system testing using the Black Box Testing method. An initial survey was also conducted among 45 respondents to determine consumer preferences regarding the use of digital platforms. The results show that the website was successfully developed with features including a product catalog, online ordering, payments via Midtrans, and integrated transaction management. Testing results indicate that all major system features function in accordance with functional requirements. Furthermore, the majority of respondents expressed interest in using digital platforms during the purchasing process and considered online reputation when making decisions. The website’s implementation has the potential to expand marketing reach, improve access to product information, and support the competitiveness of Sneew’s SMEs in the digital era. Thus, website-based digital marketing can serve as an effective alternative marketing strategy for SMEs in supporting their business’s digital transformation.